Kreatywność i innowacyjność szansą na poprawę efektywności funkcjonowania jednostek gospodarczych - Cierniak-Emerych, Anna; Golej, Robert (Creativity And Innovation as a Chance to Improve the Efficiency of Economic Units, 2005)
In the literature on the subject is pointed out, that about efficiency of functioning enterprises in more and more larger range decide such determinants and features as knowledge, creativity and innovation. In this background, the attempt to approximate the dependences occur rent between them and indicated efficiency was taken. The attention was concentrated on creativity of organization as well as her determinants. The important thing is to regard worker's creativity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 48-55